Evaluasi Efektivitas Manajemen Proyek Pemeliharaan Jalan: Studi Kasus HDM-4 Muaro Kalaban–Kiliranjao - Putra Saira, Rehan; Royhan Mashuri Harahap, Ahmad; Syafri, Yuni Purnama; Midya Octavia, Dyla; Putri Zayu, Wiwin (Civil Engineering Collaboration, 2024)
This study aims to evaluate the effectiveness of project management in national road maintenance activities based on the Highway Development and Management (HDM-4) model, using a case study of the Muaro Kalaban–Kiliranjao road section in West Sumatra Province, Indonesia. The research employs a descriptive-evaluative approach by analyzing five key elements of the Project Management Body of Knowledge (PMBOK): time, cost, quality, risk, and communication management. The data were obtained from project documentation, implementation reports, work schedules, and HDM-4 simulation outputs. The findings indicate that among the five evaluated aspects, three cost, risk, and communication are categorized as effective, while time and quality are considered moderately effective. A project delay of approximately 6% was caused by weather and logistical factors, whereas the International Roughness Index (IRI) value of 6.08 m/km remains within the acceptable technical limits of the Indonesian Highway Standard (Bina Marga). Overall, the project’s management effectiveness level reached about 80%, demonstrating that the integration of the PMBOK framework with HDM-4 analysis can improve project efficiency and economic outcomes. This research highlights the importance of structured communication systems and proactive risk mitigation strategies to enhance the performance of infrastructure projects, especially in geographically challenging areas.